Effects of coordinating support policy changes on renewable power investor choices in Europe. (January 2021) - Melliger, Marc; Lilliestam, Johan
Abstract: The economic context for renewable power in Europe is shifting: feed-in tariffs are replaced by auctioned premiums as the main support schemes. As renewables approach competitiveness, political pressure mounts to phase out support, whereas some other actors perceive a need for continued fixed-price support. We investigate how the phase-out of support or the reintroduction of feed-in tariffs would affect investors' choices for renewables through a conjoint analysis. In particular, we analyse the impact of coordination – the simultaneousness – of policy changes across countries and technologies. We find that investment choices are not strongly affected if policy changes are coordinated and returns unaffected. However, if policy changes are uncoordinated, investments shift to still supported – less mature and costlier – technologies or countries where support remains or is reintroduced. This shift is particularly strong for large investors and could potentially skew the European power mix towards an over-reliance on a single, less mature technology or specific generation region, resulting in a more expensive power system. If European countries want to change their renewable power support policies, and especially if they phase out support and expose renewables to market competition, it is important that they coordinate their actions. Highlights: Effect of coordinating support phase-out and FIT reintroduction on investor choices. Adaptive conjoint analysis to investigate impact on renewable power investments. Uncoordinated policy changes cause investment shifts if returns are unaffected. Investments shift to low price-risk options and cause a costlier power system. Reintroducing feed-in tariffs evenly distributes investment shifts among investors.